MANAGEMENT OF RADIOACTIVE WASTE FROM OPERATION OF NUCLEAR POWER PLANT -PERSPECTIVE FOR INDONESIAN PROGRAM- - Djarot Sulistio Wisnubroto (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2010)
ABSTRACTMANAGEMENT OF RADIOACTIVE WASTE FROM OPERATION OF NUCLEAR POWER PLANT -PERSPECTIVE FOR INDONESIAN PROGRAM-. Nuclear power is the only energy industry which takes full responsibility for all its wastes, and costs this into the product. Nuclear power is characterized by the very large amount of energy available from a very small amount of fuel. The amount of waste is also relatively small. It is predicted in the near future of Indonesia NPP program, about approximately 200m3 of low and intermediate level waste and 6,76m3 of spent fuel is taken each year from the core of a l000 MWe Nuclear Power Plant. There is a new option for the spent fuel management i.e. repatriation of the spent fuel to the supplier country through Global Energy Partnership (GNEP) or Developing Global Nuclear Infrastructure (DGNI) programs. Disposal methods for radioactive wastes vary in many countries. The two main options currently employed or planned by countries are, near surface disposal facilities (for short lived and low level waste); and geologic repositories (for long lived and high level waste).Keywords: radioactive waste, management, nuclear power plant, prediction, disposal ABSTRAKPENGELOLAAN LIMBAH RADIOAKTIF DARI OPERASI PEMBANGKIT LISTRIK TENAGA NUKLIR -PERSPEKTIF UNTUK PROGRAM INDONESIA. Tenaga nuklir merupakan satu-satunya industri energi yang bertanggungjawab penuh seluruh limbah yang dihasilkannya., termasuk memperhitungkan biaya limbah dalam produksi listrik. Tenaga nuklir dicirikan dengan energi yang sangat besar berasal dari kuantitas bahan bakar yang sangat kecil. Limbah yang dihasilkannya kuantitasnya juga kecil. Diprediksikan dari operasi tiap 1000MWe PLTN di Indonesia yang akan dibangun dalam waktu dekat, akan dihasilkan 200m3 limbah aktivitas rendah dan sedang serta 6,76m3 bahan bakar bekas. Ada opsi lain untuk pengelolaan bahan bakar bekas, yaitu repatriasi ke negara asal melalui program Global Energy Partnership (GNEP) atau Developing Global Nuclear Infrastructure (DGNI). Pembuangan limbah radioaktif bervariasi di berbagai negara. Dua opsi utama adalah pembuangan limbah dekat permukaan (aktivitas rendah dan sedang), dan pembuangan di lapisan geologi (limbah umur panjang dan aktivitas tinggi).Kata kunci: limbah radioaktif, pengelolaan, pembangkit listrik tenaga nuklir, prediksi, disposal